(untitled) (Rudarsko-geološko-naftni zbornik, 2021)
Interpretation of landslide kinematics provides important information for those responsible for managing the risks posed by landslides. This paper presents the interpretation of the kinematics of slow moving Kostanjek landslide, located in the urbanized area of the City of Zagreb, Croatia. The sliding material (very weak to weak marls, often covered with clayey topsoil) exhibit plastic, rather than rigid behavior. Due to this reason, and low landslide velocities, landslide features, such as main scarps or lateral flanks, are barely noticeable or do not exist in most of the landslide area. The data used for the kinematic interpretation were data from 15 GNSS sensors, for the period 2013-2019. The monitoring data revealed a different spatial and temporal distribution of landslide velocities, resulting as a consequence of geomorphological conditions and forces that govern the landslide movements. Temporally, eight periods of faster movements and seven periods of slower movements were determined. Spatially, velocities measured in the central part of the landslide were higher than on its borders. Interpretation of horizontal and vertical displacements, as well as the direction of movement, reveal the new insight into the engineering geological model and provide important information for those responsible for managing the Kostanjek landslide risk.